Case report: Incomplete laceration of the right middle lobar bronchus due to blunt chest trauma: An unusual pattern and attentions - Song, Yuqi; Ma, Jianzun; Wang, Jing; Fang, Linan (Frontiers in Surgery, 2022)
Tracheobronchial ruptures caused by blunt chest trauma are rarely encountered but may be life-threatening. It is even rarer when the rupture is in the right middle lobe bronchus. Here we present a case of incomplete laceration of the right middle lobe bronchus after blunt trauma, which could easily be overlooked because of the absence of obvious symptoms. A 58-year-old man suffered multiple traumas after being attacked by cattle, closed chest drainage was promptly performed in the local hospital for bilateral hemopneumothorax. Three days later, the patient was transferred to our center for urgent exploratory thoracic surgery due to persistent hemothorax. We did not diagnose bronchial injury even after a bedside emergency bronchoscopy due to the adherence of bloody secretions and sputum crusts. It was not until a repeat chest CT 4 days after the initial surgery that we suspected an incomplete right middle lobe bronchial laceration, which was confirmed by postoperative bronchoscopy. The patient eventually underwent right middle lobe lung resection for a deep and wide bronchial laceration and recovered well. Clinicians should be fully aware of the possibility of this condition after blunt chest trauma and make good use of CT and bronchoscopy to help with diagnosis and treatment.